Pemanfaatan Google Form untuk Audit Mutu Internal Secara Online - Muhammad Romzi; Budi Kurniawan (Universitas Mahakarya Asia, 2021)
Abstract - Internal Quality Audit (AMI) is a systematic, independent, and documented testingprocess to ensure that the implementation of activities in higher education is in accordance with procedures and the results are in accordance with standards to achieve institutional goals. Internal quality audits consist of: Document audits and field audits.Document audits are audits of the adequacy of documents at universities and SPMI documents to meet established standards. Field audits are carried out to check whether the standards set in the existing documents have been implemented properly.Document audits can be done online using a google form through a series of questions that can be submitted via a form to respondents. Respondents or auditees can show the availability of documents by attaching a softcopy file on the form. The results ofeach respondent can be seen through the results of automatic analysis on google forms which are available in the form of bar charts, pie bars, or CSV files. From the results of the existing analysis, the auditor can continue with a field audit for further checking. This study uses the R&D (Research and Development) method with a prototyping softwaredevelopment model. The R&D method is a research method used to produce certain products and test the effectiveness of these products. The result of this research is an online form containing a number of questions that are used for document audits in eachstudy program Keywords: Audit, Quality, Online, Google Form Intisari - Audit Mutu Internal (AMI) adalah proses pengujian yang sistematik, mandiri, danterdokumentasi untuk memastikan pelaksanaan kegiatan di Perguruan Tinggi sesuai prosedur dan hasilnya telah sesuai dengan standar untuk mencapai tujuan institusi. Audit mutu internal terdiri atas: Audit dokumen dan Audit lapangan Audit dokumen merupakan audit terhadap kecukupan dokumen pada perguruan tinggi sertadokumen SPMI guna memenuhi standar yang telah ditetapkan. Audit lapangan dilaksanakan untuk memeriksa apakah standar telah ditetapkan dalam dokumen yang ada telah dilaksanakan semestinya.Audit dokumen dapat dilakukan secara online dengan menggunakan google form melaluiserangkaian pertanyaan yang dapat disampaikan melalui formulir kepada para responden. Responden atau auditee dapat menujukkan ketersediaan dokumen dengan cara melampirkan softcopy file pada formulir. Respon dari masing-masing responden dapat dilihat hasilnya melalui hasil analisis otomatis pada google form yang tersedia dalam bentuk chart bar, pie bar, maupun CSV File. Dari hasil analisis yang ada, auditor dapat melanjutkan dengan audit lapangan untukpengecekan lebih lanjut. Penelitian ini menggunakan metode R&D (Research and Development) dengan permodelan pengembangan perangkat lunak prototyping. Metode R&D adalah metode penelitian yang digunakan untuk menghasilkan produk tertentu dan menguji keefektifan produk tersebut.Hasil penelitan ini adalah formulir oline yang berisi sejumlah pertanyaan yang digunakan untuk audit dokumen pada masing-masing program studi. Kata Kunci: Audit, Mutu, Online, Google Form